Direct Product and Homomorphism of Flower - Mohammed Khalid Shahoodh (Wasit Journal of Computer and Mathematics Science, 2023)
In this paper an algebraic structure namely flower has been considered. This paper presents the notation of the direct product of two flowers and studied some of its basic properties. Then, this notation has been generalized to a finite family of flowers. Furthermore, the notation of  flower homomorphism  has been also studied with some of its properties. We proved some properties in view of these notations.
Keywords: group theory; flower; homomorphism; direct product; algebraic structure